Profitability, Sales Growth, Leverage, and Tax Avoidance: The Moderating Role of Firm Size - Alya Budiantini; Flora Septiani; Rima Anjalani; Tito Sumarsono (Transpublika Publisher, 2026)
Corporate tax avoidance constitutes a persistent challenge in financial management, especially within emerging economies characterized by inconsistent regulatory frameworks and enforcement mechanisms. Within the Indonesian context, food and beverage enterprises listed on the Indonesia Stock Exchange (IDX) occupy a strategically significant position in the national economy; however, the tax compliance behavior of firms within this sector remains insufficiently examined in the existing literature. Accordingly, this study seeks to investigate the influence of profitability, sales growth, and leverage on tax avoidance, while simultaneously exploring the extent to which firm size moderates these relationships. The research is delimited to food and beverage companies listed on the IDX over the 2020-2024 observation period, employing a quantitative research design grounded in agency theory as the primary theoretical lens through which the relationships between the independent variables and tax avoidance are interpreted, with firm size serving as the moderating variable. Secondary data were collected from the audited financial statements of the sampled companies, with a total of 70 observations selected through purposive sampling. Moderated Regression Analysis (MRA) was employed as the primary analytical technique, executed using Eviews 12 software. The findings show that profitability and sales growth have a meaningful impact on tax avoidance. However, leverage does not produce a statistically significant effect. Moreover, the findings confirm that firm size acts as an important moderator, influencing how profitability, sales growth, and leverage each relate to tax avoidance.